PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ADOBE ANIMATE PADA MATA PELAJARAN DASAR-DASAR DESAIN PEMODELAN DAN INFORMASI BANGUNAN KELAS X DPIB SMK NEGERI 5 MEDAN - M Husain (STKIP Subang, 2026)
This study aimed to develop an interactive learning media based on Adobe Animate for the subject Fundamentals of Building Design Modeling and Information, particularly the Technical Drawing element, for Grade X students of the Building Design and Information Modeling (DPIB) program at SMK Negeri 5 Medan. The study was motivated by the dominant use of lecture-based teaching methods and conventional learning media, which made it difficult for students to understand abstract concepts and resulted in low participation during the learning process. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The product developed was an Adobe Animate-based interactive learning application that can be operated on Android smartphones. The validation results indicated that the interactive learning media obtained average scores of 4.29 and 4.32 from two material experts and 4.30 and 4.33 from two media experts, all of which were categorized as Highly Feasible. The practicality test showed percentages of 90% and 84% from two subject teachers and 89% from 30 students, all of which were categorized as Highly Practical. Therefore, the Adobe Animate-based interactive learning media was considered feasible and practical as a supporting learning medium. It also has the potential to increase students' learning interest and facilitate their understanding of Technical Drawing materials. This study provides an innovative alternative learning medium and supports the integration of digital technology in 21st-century education.